Mediating Role of Brand Image in the Relationship between Corporate Social Responsibility & Brand Equity: An Investigation on Unilever Bangladesh - Karim, Rashed; Fayez , Mohammed Arman (Journal of Technology Management and Business, 2020)
Corporate Social Responsibility (CSR), is one of the most discussed topics when it comes to operationalising a unique approach to do marketing and as such, create a competitive advantage for the company. Despite its popularity, CSR is not properly addressed by many Bangladeshi companies. This study sheds light upon the concept of CSR in the perspective of a multinational company, Unilever Bangladesh Limited, which has been active with their CSR initiatives for years now. This research explains the concept of CSR and discusses the dimensions of CSR (economic, social and environmental) and their benefits through the TBL paradigm. Literature has been added based on previous researches defining brand image and brand equity and addressing the relationships between CSR dimensions and brand image and brand equity. Hypotheses were then proposed to reach the research objectives of this study. Data were collected from 124 respondents through convenience sampling technique. An online-based survey was conducted due to lockdown order due to Covid-19 outbreak. The outcomes of this study confirm a significant and positive mediating effect of brand image between the relationships of economic CSR and the social CSR activities with brand equity, while the mediating effect of brand image does not exist in between the relationship of environmental CSR activities and brand equity. Finally, findings of the study may help to create a positive mindset of customers regarding the good intents of Unilever Bangladesh Limited towards Sustainable Living Plan.